Pengaruh Waktu Penambahan Lactobacillus rhamnosus SKG 34 terhadap Karakteristik Tape Ketan Probiotik Selama Penyimpanan - Dede, Emilya Grasiana; Nocianitri, Komang Ayu; Darmayanti, Luh Putu Trisna (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 3 No 1 (2018), 2018)
Tape is one of Indonesia's traditional fermented food that has a sweet and slightly sour taste. The basic ingredients of tape are materials that contain carbohydrates such as cassava and sticky rice. Lactobacillus rhamnosus SKG 34 is one type of lactic acid bacteria isolated from Sumbawa wild horse milk. This study aims to determine the best time addition of Lactobacillus rhamnosus SKG 34 and to determine the effect of the addition of Lactobacillus rhamnosus SKG 34 on the characteristic of probiotics Tape Ketan during storage. The study was conducted in two parts, namely first parts which aimed to know the difference of probiotic addition of Lactobacillus rhamnosus SKG 34 before fermentation and after fermentation. Second research was aimed to find out the viability of Lactobacillus rhamnosus SKG 34 in probiotic tape Ketan and characteristics of tape ketan during storage using Completely Randomized Design with the treatment of storage consisting of 5 levels were day 0, day 1, day 2, day 3 and day 4. The variables were LAB total, sugar total, acid total, pH and sensory characteristics. The results of this research showed that the addition of probiotics before fermentation had a higher LAB than after fermentation  (3.5 x 10 8 cfu /g). Probiotic tape Ketan  still has a good characteristic until third day  storage with characteristic LAB total 9,0 x 10 8 cfu/g, sugar total  8,17%, acid total 0,76%, pH 3,54 and color (rather like), Flavor (rather like), texture (rather like), sense hedonic test (rather like), sense scoring test (neutral) and overall acceptance (rather like).